2016
DOI: 10.1007/s00038-016-0812-1
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and hypertension care among male prisoners in Mexico City: exploring transition of care and the equivalence principle

Abstract: Continuity of care for chronic diseases, coupled with the equivalence of care principle, should provide the basis for designing chronic disease health policy for prisoners, with the goal of consistent transition of care from community to prison and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Hydrogen peroxide is used in advanced processes (APs), as hydroxyl radicals source, is the best-known AP utilizing H2O2 with ferrous/ferric ion at low pH, during which hydrogen radicals are generated. When concentration of hydrogen peroxide increased, the pH decreased [10]. As shown in fig.…”
Section: Effect Of Hydrogen Peroxide Dose On Methylene Blue Degradationmentioning
confidence: 83%
“…Hydrogen peroxide is used in advanced processes (APs), as hydroxyl radicals source, is the best-known AP utilizing H2O2 with ferrous/ferric ion at low pH, during which hydrogen radicals are generated. When concentration of hydrogen peroxide increased, the pH decreased [10]. As shown in fig.…”
Section: Effect Of Hydrogen Peroxide Dose On Methylene Blue Degradationmentioning
confidence: 83%
“…This is higher than the national prevalence of 5.8% [2,22]. Diabetes prevalence among prisoners used to be the same or lower to the national prevalence [32,34,44,46,47]. This increased diabetes could be related to poor feeding conditions and sedentary lifestyle.…”
Section: Discussionmentioning
confidence: 94%
“…Evidence from western countries shows that noncommunicable disease (NCD) is a public health problem in prison [34,35,[41][42][43][44][45]. Recent studies in Africa showed an increased prevalence of NCD among prisoners [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two different settings used continuity as a concept in the context of ‘transition of care’, namely chronic disease care and management for prisoners to ensure consistent transition of care from community to prison and back [29] and the transition of care for children with chronic diseases moving from paediatric to adolescent to adult clinical settings [30–32]. The children’s transition process was described either as a CoC in two empirical studies from Brazil and Thailand [30, 31], or as a continuum of care in one review [32].…”
Section: Resultsmentioning
confidence: 99%